(untitled) (Bangladesh Journal of Otorhinolaryngology, 2016)
Nowadays, tuberculosis (TB) infection shows re-emergence again in many other part of the world due to HIV/AIDS- related disease, low socioeconomic as well as insurgence of multidrug resistance tuberculosis. TB is a disease which is primarily affects a lung. However it also can affect other organs as a secondary disease in a body via hematogenous or lymphatic spread. As in ENT field, TB also can manifest as a solely ear, nose or throat (ENT) diseasea such as in primary laryngeal tuberculosis (TB). In the past, laryngeal TB typically presented as a secondary disease with ulcerated laryngeal lesions in advanced pulmonary tuberculosis patient. In our case, we report a case of primary laryngeal tuberculosis masquerading as laryngeal malignancy in adult patient without pulmonary tuberculosis. In conclusion, in a patient who presented with various laryngeal symptoms, physician should be aware of the reemergence of laryngeal tuberculosis and the various manisfestation of the disease. Bangladesh J Otorhinolaryngol; October 2015; 21(2): 122-128